(untitled) (Research, Society and Development, 2021)
The COVID-19 pandemic brought numerous stressful factors to the population, causing an increase in violence against children and adolescents. The objective of this work was to verify the incidence of domestic physical violence against children and adolescents in a city in the interior of Bahia during the COVID-19 pandemic. This is a cross-sectional quantitative study, where the research data were obtained through the Information Technology Department of the Unified Health System, from the Information System for Notifiable Diseases, for data collection, the notifications were considered. year 2019. The sample consisted of 658 cases of domestic physical violence. The main place of occurrence was the residence (357 cases) which occurred with female adolescents (368 cases), aged from 15 to 19 years (69 cases), of mixed race/color (198 cases). With regard to parenteral intercourse, 268 cases were committed by adults, where 87 cases were committed by the ex-spouse. Regarding the evolution of the case, despite the existence of such a variable, this information was filled in as blank and ignored. It was possible to conclude with this study that violence against children and adolescents grew significantly during the COVID-19 pandemic, and it is also possible to observe the need for current work on the subject, in addition, it is important to emphasize the need for correct and complete filling in the notification form.